PENGARUH PERSEPSI HARGA, KEPERCAYAAN, DAN ORIENTASI BELANJA TERHADAP NIAT BELI SECARA ONLINE (STUDI PADA PRODUK FASHION ONLINE DI KOTA DENPASAR) - Nusarika, Luh Alviolita Kusuma; Purnami, Ni Made (E-Jurnal Manajemen, 2015)
The purpose of this study were (1) to analyze the influence of the perception of the price of the purchase intention of fashion products online in Denpasar, (2) to determine the effect of confidence on the product's purchase intention of fashion products online in Denpasar and (3) to determine the effect on the intention of shopping orientation and purchase products online fashion in Denpasar. This research was done by using multiple linear regression data analysis. The number of samples obtained by using purposive sampling method is a total of 112 respondents. Based on the results of the analysis can be argued that the price perceptions, beliefs and orientations simultaneously affect expenditure on purchase intention of fashion products online in Denpasar with Fhitung value (118.509) with sig (0,000). price perceptions, beliefs and orientations shopping partial significant positive effect on purchase intention of fashion products online in Denpasar. Suggestions can be recommended for online shopping providers are expected to provide information that is clear, complete and accurate information on the procedures for product ordering and payment, shipping and returns procedures, or exchange the product. Online product sellers should pay attention and keep better confidence in the services provided to consumers regarding the suitability of the goods sold by the fully informed.
Keywords: persepsi harga, kepercayaan, orientasi belanja, niat beli